135 CLINICAL APPLICATION AND REPRODUCIBILITY OF CENTRAL PRESSURE AUGMENTATION USING RADIAL ARTERY PULSE WAVE ANALYSIS. (24th May 2013) - Kotecha, D; Pepper, J; Flather, M D
Abstract : Background: The use of surrogate measures for central artery blood pressure (BP) is now commonplace, including radial artery pulse wave analysis (PWA). Prior studies have examined central augmentation index (cAI), defined as the systolic augmentation pressure (cAP)/pulse pressure. We sought to assess the validity, reproducibility and clinical utility of systolic and diastolic parameters. Methods: 346 patients attending elective coronary angiography were pre-assessed with conventional sphygmomanometry and radial PWA, with direct aortic BP taken during cardiac catheterisation. Results: PWA-derived central systolic BP was closer to measured pressure (2.70 mm Hg lower; SE=1.18) compared to conventional BP (8.03 mm Hg higher; SE=1.22). However for diastolic BP, conventional and PWA measurement were similar and higher than aortic pressures (9.93 and 10.99 mm Hg; SE for both 0.83). cAP was linearly associated with age (r=0.40, p<0.001), whereas pulse pressure and cAI had a curvilinear relationship, with the latter showing no relationship to the Framingham Risk Score. Reproducibility assessment identified broader limits of agreement for cAI than cAP (see figure) although similar coefficients of variation (10%). cAP, derived solely from systole, was significantly associated with both the extent and severity of angiographic coronary disease after adjusting for risk factors, unlike cAI (see table).Figure 1 Conclusions: Radial artery PWA is a valid and reproducible method of estimating central systolic BP parameters and central augmentation pressure is independently associated with coronary atherosclerosis. Variation in diastolic waveforms limits the use of augmentation index for risk stratification of patients with suspected coronary artery disease.